DAMPAK KEBIJAKAN FISKAL TERHADAP KINERJA SEKTOR PERTANIAN DI SULAWESI TENGGARA - Jabuddin, La Ode; Padangaran, Ayub M; Bafadal, Azhar Bafadal (Jurnal Sosio Agribisnis, 2016)
This study aims to: (1) Knowing the dynamics of fiscal policy and the performance of the agricultural sector, (2) Analyze the factors that influence fiscal policy and the performance                   of the agricultural sector, and (3) Analyzing the impact of fiscal policy on the performance of the agricultural sector. The data used in this study were pooled 2005-2013 data in the aggregate. Econometric model the impact of fiscal policy on the performance of the agricultural sector is built in the form of simultaneous equations, consisting of 7 equations with 25 total variables in the model, 7 endogenous variables, 12 exogenous variables, and 6 variables lag. The model is estimated by 2SLS method SYSLIN procedures and historical simulation with SIMNLIN procedure.The results showed that: (1) The development of fiscal policy in Southeast Sulawesi from year to year tends to increase, (2) The performance of the agricultural sector from the aspect of GDP has decreased, from the aspect of labor is still consistent, in terms of investment to grow positively, and assign roles which means to decrease the number of poor people, (3) factors affecting fiscal policy is local revenues, equalization funds, other revenues, as well as the lag fiscal policy, (4) the factors that affect the performance of the agricultural sector from the aspect GDP is labor, direct expenditure and GDP lag; from the aspect of labor is the total labor force, investment, land area, direct expenditure, as well as the lag of labor; from the aspect of investment is influenced by GDP per capita, land area, interest rates and investment lag; as well as from the aspect of poor people, are affected by population, investments, direct expenditure and poverty lag, (5). Fiscal policy impact on the agricultural sector GDP increase, a decrease in the number of poor, declining agricultural laborers, and a decrease in the amount of investment in the agricultural sector.Keywords: Fiscal policy, the performance of the agricultural sector, the simultaneous equations